Effects of plant diversity on the concentration of secondary plant metabolites and the density of arthropods on focal plants in the field. (19th December 2016) - Kostenko, Olga; Mulder, Patrick P. J.; Courbois, Matthijs; Bezemer, T. Martijn
Summary: The diversity of the surrounding plant community can directly affect the abundance of insects on a focal plant as well as the size and quality of that focal plant. However, to what extent the effects of plant diversity on the arthropod community on a focal plant are mediated by host plant quality or by the diversity of the surrounding plants remains unresolved. In the field, we sampled arthropod communities on focal Jacobaea vulgaris plants growing in experimental plant communities that were maintained at different levels of diversity (one, two, four or nine species) for 3 years. Focal plants were also planted in plots without surrounding vegetation. We recorded the structural characteristics of each of the surrounding plant communities as well as the growth, and primary and secondary chemistry (pyrrolizidine alkaloids, PAs) of the focal plants to disentangle the potential mechanisms causing the diversity effects. Two years after planting, the abundance of arthropods on focal plants that were still in the vegetative stage decreased with increasing plant diversity, while the abundance of arthropods on reproductive focal plants was not significantly affected by the diversity of the neighbouring community. The size of both vegetative and reproductive focal plants was not significantly affected by the diversity of the neighbouring community, but the levels of PAs and the foliar N concentration of vegetative focal plants decreased with increasing plant diversity. Structural equation modelling revealed that the effects of plant diversity on the arthropod communities on focal plants were not mediated by changes in plant quality. Synthesis . Plant quality can greatly influence insect preference and performance. However, under natural conditions, the effects of the neighbouring plant community can overrule the plant quality effects of individual plants growing in those communities on the abundance of insects associated to this plant. Abstract : Plant quality can greatly influence insect preference and performance. However, under natural conditions, the effects of the neighbouring plant community can overrule the plant quality effects of individual plants growing in those communities on the abundance of insects associated to this plant.